Improving equity through fiscal policy : dashed dreams - Fudge, Marc; Holzer, Marc (Routledge, 2026)
"Improving Equity through Fiscal Policy: Dashed Dreams explores the delivery of key services to the public and to what extent equity is considered when government allocates resources. Authors Marc Fudge and Marc Holzer examine the key topics in a typical public budgeting, finance, or policy course including taxation, public choice, and political economics from an equity-based lens. They then offer a deep dive into the development of US public policies, tackling a complex history of policies written expressly to undermine or suppress the advancement of Blacks and People of Color. The result is a timely supplement to public budgeting and finance courses that encourages readers to recognize and reckon with the persistence of deep disparities - and the ways in which contemporary public budgeting cannot be understood without considering equity. The book begins with a discussion of the value of social equity and how it emerged as a critical component of public administration and policy. It then provides coverage of the economic role of government in society, taxation and its distributional effects, voter suppression, as well as inequities in housing, education, and health. It further explores the racial wealth gap as well as positive examples of strategies that have helped to support a fairer and more equal allocation of resources. Improving Equity through Fiscal Policy: Dashed Dreams offers instructors, students, policy makers, elected officials, managers, and leaders a critical and necessary re-examination of this important topic"-- Provided by publisher.
Keywords: Fiscal policy -- Social aspects -- United States.; Finance, Public -- Social aspects -- United States.; Income distribution -- Social aspects -- United States.; Equality -- Economic aspects -- United States.; African Americans -- Economic conditions -- 21st century.; Minorities -- United States -- Economic conditions -- 21st century.; elektronické knihy; electronic books